Using appreciative inquiry as a tool for revitalizing community Organisations: A case study of WISALTS Inc - Paulin, S.; Dhakal, Subas (2011)
WISALTS Inc. is one of the oldest Environmental Community Organisations (ECOs) active in Western Australia (WA). The organisation has been tackling the issue of land degradation in the agricultural areas since 1978. However, declining membership as well as the departure of key leaders has cast uncertainty over its future. It has been argued that the Appreciative Inquiry (AI) approach has the potential to induce sustainable transformative change within organisations. Grounded in the theory of social constructionism, AI is a different approach to organisational development; one that focuses on past strengths and successes rather than the weaknesses and failures. In this context, this paper discusses the principles and processes of AI and explores its use in supporting a lifespan change process within WISALTS Inc., as a case study.